2012
DOI: 10.1021/np300465f
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrozingerone, a Structural Analogue of Curcumin, Induces Cell-Cycle Arrest at the G2/M Phase and Accumulates Intracellular ROS in HT-29 Human Colon Cancer Cells

Abstract: Dehydrozingerone (1) is a pungent constituent present in the rhizomes of ginger (Zingiber officinale) and belongs structurally to the vanillyl ketone class. It is a representative of half the chemical structure of curcumin (2), which is an antioxidative yellow pigment obtained from the rhizomes of turmeric (Curcuma longa). Numerous studies have suggested that 2 is a promising phytochemical for the inhibition of malignant tumors, including colon cancer. On the other hand, there have been few studies on the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 44 publications
1
53
0
Order By: Relevance
“…It is quite interesting to note that the same dose of ginger extract is required for inducing highest apoptotic activity in the cancer cells ( Figures 1A and 3B), This could suggest that 3mg/ml is a very effective dose of ginger extract for optimized anti-cancer effect on colon adenocarcinoma. Other studies have also reported the anti proliferative property of ginger extract in colon cancer cells lines HCT 15 and HT 29 (Kim et al, 2008;Lee et al, 2008;Yogosawa et al, 2012). We have previously demonstrated that ginger extract inhibited the growth of HepG2 hepatoma cells and the formation of tumor in liver cancer-induced rats (Mohd Yusof et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…It is quite interesting to note that the same dose of ginger extract is required for inducing highest apoptotic activity in the cancer cells ( Figures 1A and 3B), This could suggest that 3mg/ml is a very effective dose of ginger extract for optimized anti-cancer effect on colon adenocarcinoma. Other studies have also reported the anti proliferative property of ginger extract in colon cancer cells lines HCT 15 and HT 29 (Kim et al, 2008;Lee et al, 2008;Yogosawa et al, 2012). We have previously demonstrated that ginger extract inhibited the growth of HepG2 hepatoma cells and the formation of tumor in liver cancer-induced rats (Mohd Yusof et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…Structurally, it is representative of half the chemical structure of curcumin which is a promising phytochemical for the inhibition of malignant tumours, including colon cancer. Yogosawa et al (2012) evaluated the antiproliferative effects of dehydrozingerone against HT-29 human colon cancer cells, and it was found that it dose-dependently inhibited growth at the G2/M phase with up-regulation of p21. Dehydrozingerone additionally led to the accumulation of intracellular ROS, although most radical scavengers could not clearly repress the cell-cycle arrest at the G2/M phase.…”
Section: Zingiber Officinale Roscoe (Family Zingiberaceae) Gingermentioning
confidence: 99%
“…However, other antioxidants did not reverse the effects of dehydrozingerone on cell cycle arrest. The authors indicate that further studies are required to confirm the involvement of ROS, since dehydrozingerone is structurally similar to curcumin and could conjugate with glutathione, the direct metabolite of N-acetyl-L-cysteine to reduce its potency in the cell [29]. A study on the anticancer effects of curcuminoids in both HT-29 and SW480 colon cancer cells and CCD-18Co colon fibroblasts reported inhibition of HT-29 and SW480 colon cancer cell growth and enhanced activity of the chemotherapeutic agent 5-fluorouracil.…”
Section: Ros and Cancer Therapymentioning
confidence: 99%